Procedimentos de treino e teste de relações entre estímulos em Cebus apella - BRINO, Ana Leda de Faria (Universidade Federal do Pará, 2011)
Complex learning encompasses the control by abstract relations after some relations have been directly trained. In these work, a sequence of experiments investigated stimulus relations learning in two capuchin-monkeys (Cebus apella) involving direct training of identity relations, successive tests of generalized identity, direct training of arbitrary relations, and test for symmetric relations as indication of equivalence class formation. Three theoretical foundations were followed: 1) Equivalence class formation is a basic stimulus function; 2) Stimulus control topography coherence theory; and 3) A version of the personalized system of instruction as an alternative to establish relational repertoires in non-verbal organisms. The subjects presented high levels of performance in identity and arbitrary conditional discriminations. The subjects given generalized identity tests demonstrated that abstract relation; the subject given arbitrary training presented negative results in the test for symmetric performances. Stimulus relations learning problems found here with nonhuman subjects seem to be similar to that presented by human individuals with retarded development. Teaching procedures for retarded individuals were sufficient to solve most repertoire deficiencies of non-humans, which are usually attributed to species limitations.